Procalcitonin fails to predict bacteremia in SIRS patients: a cohort study. Issue 10 (4th June 2014) - Hoenigl, M.; Raggam, R. B.; Wagner, J.; Prueller, F.; Grisold, A. J.; Leitner, E.; Seeber, K.; Prattes, J.; Valentin, T.; Zollner‐Schwetz, I.; Schilcher, G.; Krause, R.
Summary Background Procalcitonin (PCT) has previously been proposed as useful marker to rule out bloodstream‐infection (BSI). The objective of this study was to evaluate the sensitivity of different PCT cut‐offs for prediction of BSI in patients with community (CA)‐ and hospital‐acquired (HA)‐BSI. Methods A total of 898 patients fulfilling systemic‐inflammatory‐response‐syndrome (SIRS) criteria were enrolled in this prospective cohort study at the Medical University of Graz, Austria. Of those 666 patients had positive blood cultures (282 CA‐BSI, 384 HA‐BSI, enrolled between January 2011 and December 2012) and 232 negative blood cultures (enrolled between January 2011 and July 2011 at the emergency department). Blood samples for determination of laboratory infection markers (e.g. PCT) were collected simultaneously with blood cultures. Results Procalcitonin was significantly (p < 0.001) higher in SIRS patients with bacteremia/fungemia than in those without. Receiver operating characteristic curve analysis revealed an area under the curve (AUC) value of 0.675 for PCT (95% CI 0.636–0.714) for differentiating patients with BSI from those without. AUC for IL‐6 was 0.558 (95% CI 0.515–0.600). However, even at the lowest cut‐off evaluated (i.e. 0.1 ng/ml) PCT failed to predict BSI in 7% (n = 46) of patients. In the group of patients with SIRS and negative blood culture 79% (n = 185) had PCT levels > 0.1. Conclusion Procalcitonin was significantly higher in patients with BSI than in those without and superior to IL‐6 and CRP. The clinical importance of this is questionable, because a suitable PCT threshold for excluding BSI was not established. An approach where blood cultures are guided by PCT only can therefore not be recommended.